SISTEM INFORMASI SIMPAN PINJAM DI KOPERASI WANITA AZ-ZAKINAH BONDOWOSO MENGGUNAKAN PHP DAN MySQL - Auliatur Rahmah (Jurnal Ilmiah Informatika, 2018)
The saving and loan information system that is run in Az-Zakinah Cooperatives is a kind of saving and loan enterprise. It gives service to all the members particularly those in the saving and loan cooperatives. The data management is still made and written in a book, so any members who want to do saving or loan should wait in a long time because the service is not as fast as a computerized process. It is then expected to help the cooperatives in cases of their service to their members, their data management i.e. saving the data and other documents to make the service faster and more accurate. The method used in developing the information system of saving and loan applies Diagram Context, Data of Flow Diagram and application tools, and a proposed database entity relation diagram table relation. The technique of data collection applies observation and interview. The program implementation uses PHP and MySQL programming. The designed information system of saving and loan aims at building a computerized information system to facilitate the cooperative's employees in the cases of the member data management, the data of saving, the data of loan, and the data of installment.